PERGESERAN KEKUASAAN PRESIDEN DI BIDANG PERUNDANG-UNDANGAN SETELAH AMANDEMEN UUD 1945 - W.M. Herry Susilowati (Institute for Research and Community Services (LPPM) of Wijaya Kusuma Surabaya University, 2004)
After changing Paragraph 5-article (1) and Paragraph 20 article (1) of UUD 1945 in 1999 as the first change on UUD 1945, then in practice there is a changed nuance on legislative power implementation in Republic of Indonesia. Initially as the main decision-maker; president had the right to formulate decree but then the right is given to Indonesian Legislative Assembly (DPR) without leaving cooperative relation between them. The results of the power shift asserts the function of Indonesian Legislative Assembly on decree making, so that they must be able to be initiators on every process of decree making. It is this claim that has been the pursuits of democratic life for this long and will provide larger authority to the parliament on state law suite to adjust parliament authority and government.